MEMBANGUN KESADARAN HUKUM BAGI MASYARAKAT DAN PENGAK HUKUM AGAR TERCIPTA PENEGAKAN HUKUM YANG BERKEADILAN - Ach. Fadlail (HUKMY : Jurnal Hukum, 2023)
Legal conformity, legal design, and legal validity are often associated with legal awareness. Legal awareness is a perception of human value in relation to applicable law. Our society's legal awareness recognizes that the rule of law regulates living together and provides a basis for resolving problems posed by the risks of living together. Furthermore, law enforcement is the process of making efforts to uphold or function legal norms in a real way as a guideline for behavior in traffic or legal relations in the life of society and the state. Stable security conditions will support law enforcement efforts in creating a just law, and law enforcement will support the creation of public order and security. Public trust in the legal system will recover in terms of substance, structure and legal culture if the embodiment of the values ​​of justice and truth is achieved through law enforcement that is straightforward, firm and indiscriminate, and does not have the character of KKN (Corruption, Collusion and Nepotism). The fundamental role of law as a central point in constitutional and social life towards a just, prosperous and prosperous life is one of the foundations of a rule of law. However, building a legal culture in this country is very challenging from a material perspective. There are several factors that influence this situation, including: 1) legal aspects; 2) law enforcement aspects; 3) facilities and institutions; 4) community aspect; and 5) cultural aspects.